2019
DOI: 10.21873/anticanres.13822
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor Effects of Cyclolinopeptide on Giant-cell Tumor of the Bone

Abstract: Aim: This study aimed to evaluate the antitumor effects of cyclolinopeptide (CL), which suppresses receptor activator of nuclear factor-ĸB ligand (RANKL) signalling on giant-cell tumours of the bone (GCTB) cells. Materials and Methods: GCTB cell lines were established, and the inhibition of cell growth by CL was evaluated using the water-soluble tetrazolium salt-8 cell proliferation assay, cell cycle assay, and 5-ethynyl-2'-deoxyuridine (EdU) cell proliferation assay. RANKL and runt-related transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Furthermore, cytotoxicity of this compound was not found in non-malignant cells, peritoneal macrophages ( Figure 1H). Similarly, other natural bioactive orbitides such as surfactins and beauvericin displayed anti-cancer activity in giant-cell tumors of the bone (GCTB) cells, MCF-7 breast tumor cells, and CT-26 lymphoma [38][39][40], implying that cytotoxic activity of LOB3 might be due to structural feature of this compound. Taken together, these results suggest that LOB3 plays an anti-cancer role by inducing cytotoxicity and reducing the proliferation of cancer cells).…”
Section: Cytotoxic and Anti-proliferative Effect Of Lob3 In Cancer Cellsmentioning
confidence: 99%
“…Furthermore, cytotoxicity of this compound was not found in non-malignant cells, peritoneal macrophages ( Figure 1H). Similarly, other natural bioactive orbitides such as surfactins and beauvericin displayed anti-cancer activity in giant-cell tumors of the bone (GCTB) cells, MCF-7 breast tumor cells, and CT-26 lymphoma [38][39][40], implying that cytotoxic activity of LOB3 might be due to structural feature of this compound. Taken together, these results suggest that LOB3 plays an anti-cancer role by inducing cytotoxicity and reducing the proliferation of cancer cells).…”
Section: Cytotoxic and Anti-proliferative Effect Of Lob3 In Cancer Cellsmentioning
confidence: 99%
“…Such property could be of advantage in delaying progress of osteoporosis. In addition, CLA was shown to inhibit growth of bone giant cell tumor by arresting cells in G0/G1 phase of cell cycle [23]. Of interest, our data from an investigation on 13-week toxicity in rats (unpublished) revealed that CLA lowered serum cholesterol level, albeit only in females.…”
Section: Other Biological Activities Of Clamentioning
confidence: 88%
“…The immunosuppressive actions of CLA and some of its analogs are presented in Table 1. cyclolinopeptide A suppression of: graft-versus-host reaction, allogeneic graft rejection, post-adjuvant polyarthritis, humoral and cellular immune response and reduction of hemolytic anemia in New Zealand Black mice [4] cyclolinopeptide A inhibition of human Plasmodium falciparum growth in culture [21] cyclolinopeptide A inhibition of osteoclast differentiation [22] cyclolinopeptide A inhibition of bone giant cell tumor growth [23] H…”
Section: Other Biological Activities Of Clamentioning
confidence: 99%
“…Such property could be of advantage in delaying progress of osteoporosis. In addition, CLA was shown to inhibit growth of bone giant cell tumor by arresting cells in G0/G1 phase of cell cycle [ 23 ]. Interestingly, our data from an investigation on 13-week toxicity in rats (unpublished) revealed that CLA lowered serum cholesterol level, albeit only in females.…”
Section: Other Biological Activities Of Clamentioning
confidence: 99%